(untitled) - Coscarelli, William C. (San Francisco, Calif., 2007)
Decision-making skills are mission-critical in today's competitive environment, and a prerequisite for leadership advancement. Boost them with the Decision-Making Style Inventory (DMI).
Keywords: Decision making,Ra quyết định; Testing,Kiểm tra